2011
DOI: 10.1007/s00520-010-1070-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related symptom clusters for symptom management in outpatients after commencing adjuvant chemotherapy, at 6 months, and 12 months

Abstract: Stability is a necessary attribute of symptom clusters, but definitional clarification is required. We propose that a core set of concurrent symptoms identifies each symptom cluster, signifying a common cause. Additional related symptoms may be included over time. Further longitudinal investigation is required to identify symptom clusters and the underlying causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 35 publications
(49 reference statements)
3
54
0
1
Order By: Relevance
“…Sleep disturbance and insomnia were not included in the cluster configuration, as they were rarely abstracted from patients’ charts (but likely were significant issues for hospitalized patients). Skerman and colleagues 54 reported the association of sleep, fatigue, and pain. However, no psychosocial variables were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbance and insomnia were not included in the cluster configuration, as they were rarely abstracted from patients’ charts (but likely were significant issues for hospitalized patients). Skerman and colleagues 54 reported the association of sleep, fatigue, and pain. However, no psychosocial variables were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of sadness or depression was one of numerous psychosocial variables included in some studies, 5, 53 was listed as “psychological distress” in others, 8, 55 and was not evaluated in another. 54 In addition, psychological symptoms have many different connotations which vary considerably based on the verbiage chosen for particular symptom checklists. Likewise, the clustering of pain varied among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using qualitative research methods (34)(35)(36)(37), several groups of interlinked symptoms were identified de novo through interviews with oncology patients. In several quantitative studies (38)(39)(40)(41)(42), a variety of statistical approaches (eg, factor analysis [FA], hierarchical cluster analysis [HCA], principal components analysis [PCA]) were used to identify symptom clusters de novo. The outcome of these types of analyses is the de novo identification of one or more symptom clusters, each of which contains two or more symptoms.…”
Section: Identification Of Symptom Clustersmentioning
confidence: 99%
“…Yet the objective in this study was to consider multi-symptoms instead of single-symptom burden. Previous research has shown that multiple symptoms (some of them in clusters) may be experienced by the majority of patients receiving chemotherapy (Thomas et al, 2014;Skerman et al, 2012), and it was this cumulative effect of multiple symptoms on anxiety levels that we wished to investigate here. Investigation of the links between single chemotherapy-related symptoms and state/trait anxiety levels is nevertheless warranted.…”
Section: Limitations and Future Researchmentioning
confidence: 99%